Smart Lighting and Interior Blinds Control through IoT - Makkar, Deepak; Syal, Poonam (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, energy usage is increasing due to higher demand than its supply. The electrical energy is mostly utilised in the form of lighting in commercial and residential buildings. The traditional illuminance system uses more electricity than light emitting diode (LED) used in the intelligent lighting system. As the dimming of LEDs can save the extra energy. Therefore, the energy efficient lighting provides better utilisation of the electrical energy. The prime objective of the work presented in this paper is to model intelligent LED lighting system prototype to generate light of the required illuminance level in a room considering energy efficiency and comfort with the integration of daylight. In this system the softwares viz. Proteus and Arduino IDE have been used to evaluate the functioning of the prototype. This lighting system can be monitored online through IoT Platform.